EXPLORING THE PROPHET MUHAMMAD'S (PBUH) RECOMMENDATION OF KALONJI AND ITS RELEVANCE IN MODERN DISEASE MANAGEMENT: A COMPREHENSIVE REVIEW - Md Tauhid Alam; Alam, Md. Tanwir; Akhtar, Jamal; Anjum, Sultana (International Islamic Medicine Forum, 2025)
The seed of Nigella sativa Linn., known by various names like Small Black Seed, Black Cumin, and Kalonji, has a rich history in treating diverse ailments, as lauded by Prophet Mohammad (PBUH) for its healing properties against numerous diseases, except death, in Islamic and Arabic traditions. Rich in volatile oils, fixed oils, tannins, proteins, and essential amino acids, Kalonji finds extensive use in Unani medicine for conditions ranging from joint pain and indigestion to asthma, diabetes, and even cancer. This review synthesizes current literature to explore Kalonji's therapeutic potential, emphasizing its historical significance and relevance in modern disease management. By elucidating its multifaceted applications, from traditional remedies to contemporary pharmacology, the review contributes to a comprehensive understanding of Kalonji's role in healthcare today.